Development of Literacy-Based Performance Assessment Instruments to Improve Communication Skills in Thematic Learning of Class V - Arsy Dilivia Fitri; Munaris Munaris; Caswita Caswita (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
This research aims to (1) produce performance assessment instruments based on literacy that meet the standards (theoretically feasible, practical, valid, and reliable) on thematic learning of grade V elementary school, and (2) produce performance assessment instruments based on literacy that can effectively improve communication skills in thematic learning of grade V elementary school. The research population is all class V learners at 5 State Elementary Schools in Ngurah Rai Cluster seputih Raman District of Central Lampung Regency which amounted to 148 learners. This study uses nonprobability sampling with a type of purposive sampling technique that is a sample determination technique with certain considerations. The data collection techniques used in this study are interviews, questionnaires, observations and documents. The instruments used in the study used nontes. Data analysis techniques used include analysis of validity, reliability, and effectiveness. The results of this study show that (1) istrumen performance assessment based on literacy to improve communication skills developed proven to meet standards (theoretically and practically feasible). (2) iinstrument performance assessment based on reading literacy produced effectively can improve to improve communication skills in thematic learning class V elementary school.